2016
DOI: 10.1155/2016/9413879
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Adsorption of Heavy Metals onto Spent Coffee Ground: Equilibrium, Regeneration, and Dynamic Performance in a Fixed-Bed Column

Abstract: Equilibrium and dynamic adsorption of heavy metals onto spent coffee ground (SCG) were studied. The equilibrium adsorption of Cd2+, Cu2+, and Pb2+in a batch system was modeled by an ion-exchange model (IEM) based on an ion-exchange of heavy metals with calcium and protons bonded to active sites on SCG surface. The maximum amount of adsorbed metal ions obtained using the IEM was 0.12, 0.21, and 0.32 mmol/g of Cd2+, Cu2+, and Pb2+, respectively. Regeneration of SCG was evaluated using citric acid, calcium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…After adsorption of Ni 2+ or Cd 2+ at a concentration of 80 ppm, desorption of the metal from the bead was performed using 0.1 M HNO 3 . Nitric acid at a concentration of 0.1 M has been used before for desorption of heavy metals from the SCGs with high desorption efficiency [47]. The effect of time in the percent of desorption was studied in the first cycle of desorption and it can be seen in Figure 15.…”
Section: Adsorption/desorption Studiesmentioning
confidence: 99%
“…After adsorption of Ni 2+ or Cd 2+ at a concentration of 80 ppm, desorption of the metal from the bead was performed using 0.1 M HNO 3 . Nitric acid at a concentration of 0.1 M has been used before for desorption of heavy metals from the SCGs with high desorption efficiency [47]. The effect of time in the percent of desorption was studied in the first cycle of desorption and it can be seen in Figure 15.…”
Section: Adsorption/desorption Studiesmentioning
confidence: 99%
“…The presence of lignin was confirmed in the broad band at 3305.93 (Arabica) and 3248.24 (Robusta) cm -1 , which is mainly attributed to O-H and N-H stretching [15]. The peak present in 1012 (Arabica) and 1030.89 (Robusta) cm -1 is attributed to the presence of lignin and cellulose due to C-O deformation [16]. Lignocellulosic materials are used in removing contaminants in water [17].…”
Section: Resultsmentioning
confidence: 87%
“…The increase in the value of the breakthrough time is caused by the high dose of adsorbent in the column which resulted to the increase of possible active sites for copper adsorption [16].…”
Section: B Adsorbent Characterizationmentioning
confidence: 99%
“…Compared to the wealth of literature on equilibrium and kinetic parameters for mass transfer, relatively few papers have considered sensitivity to heat transfer parameters 9,21,23,31,[40][41][42][43] . This is partially due to the simplifying assumption made in many studies [2][3][4][5][6][7][8][10][11][12][13][14][15][16][17][24][25][26]30,32,34 to neglect heat transfer and treat the entire bed as isothermal. This assumption is made despite the fact that system-level models of cyclic pressure and temperature-swing-adsorption processes are known to be highly sensitive to temperature variations 20 .…”
Section: Axial Dispersion Is a Complex Function Of Flow Conditions Anmentioning
confidence: 99%
“…Conclusions in the literature regarding sensitivity to axial dispersion are less consistent; while many researchers concluded that adsorption models are insensitive to axial dispersion 3,4,10,12,14,21,26,30 , others found the opposite to be true 16,24,25,33 . Yet others are equivocal in their conclusions.…”
Section: Introductionmentioning
confidence: 98%